Adrenocortical carcinoma in a pediatric patient with li-fraumeni-like Syndrome: an endemic condition in southern Brazil - Mendes Knabben, Mariana; Reis Caldas, Renan; Onofre de Brito Lima, Jéssica; Spader Casagrande, Aline; Lorenzoni Almeida Ghezzi, Caroline (Clinical and Biomedical Research, 2021)
A 12-year-old boy with germline TP53-R337H mutation and family history of early adrenocortical carcinoma (ACC) was admitted to hospital with abdominal pain and distention. During the physical examination he presented cushingoid facies, high blood pressure and pulse rate. The endocrine examination showed elevated serum cortisol, suppressed plasma adrenocorticotropic hormone and loss of circadian rhythm. Abdominal ultrasound and computed tomography (CT) revealed a heterogeneous mass in the right adrenal gland with 13.5 x 10.4 x 9.4 cm sized and calcifications (Fig. 1 and 2). The tumor extended via an intrahepatic segment of inferior vein cava directly into the right atrium (Fig. 2). Histological examination of the specimen revealed an adrenocortical tumor with high mitotic rate, atypical mitotic figures, necrosis and a diffuse proliferation of large polygonal and eosinophilic neoplastic cells, related to adrenocortical carcinoma (fig. 3). The patient deteriorate despite chemotherapy and died in a few months. Adrenal lesions are common and seen in 3–10% of the population, frequently an incidental finding and benign prognosis. In contrast, adrenocortical malignancies are very rare, with a maximum incidence between 40 and 50 years of age. It is even rarer in children and it is typically associated with two genetic syndromes: Beckwith-Wiedemann and Li-Fraumeni (LFS). (1) The incidence of ACC in children in southern Brazil is 2.9 - 4.2 cases/ million/year, while the worldwide is approximately 0.2 - 0.3 cases/million/year. The difference of prevalence in that geographical region is related to a specific germline TP53 mutation (R337H), a low penetrance mutation that shown distinct phenotypes in different families, has been reported to be associated with ACC in children and other forms of cancer in the LFS spectrum. The incidence of this mutation in southern Brazil is 1:300 individuals in the general population, while in Europe and North America it is 1:2000 - 1:5000 people. (2) The LFS and similar phenotypes are characterized by an autosomal dominant inheritance pattern linked to a mutation in the TP53 tumor suppressor gene, associated with the diagnosis of various tumor types at a young age, such as ACC, breast cancer, central nervous system tumors, osteosarcomas and soft-tissue sarcomas. (3) The diagnosis of cancer has a bimodal age distribution, with the highest peak before the age of 10 and a second peak between 30-50 years old. In a study conducted in Southern Brazil were observed that 25% of pediatric patients with tumors related to LFS spectrum, fulfill clinical criteria for these syndromes.(4) Genetic tests are now more advanced and available, it becomes more common to diagnose genetic syndromes that increase the predisposition of neoplasms. Imaging tests can be useful in their screening and early diagnosis, with an impact on treatment and prognosis. The screening protocol proposed for patients with the germline TP53 mutation involves abdominal ultrasound, urinalysis, and blood test every 3-4 months and whole-body and brain MRIs once a year. (4) Highlighting that every children with ACC, especially in the endemic area of Brazil, should be investigated for the LFS for proper genetic counseling and management of families.